Types and severity of physical impairments of para taekwondo athletes - Davalli, A.; O'Sullivan, D. M.; Stefano, B.; Jeong, H. S. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Para taekwondo has only recently been added to the Paralympic games scheduled to be held in 2021; however, there is limited research on the classification of the para taekwondo athletes. This study aimed to provide details on the impairments and disabilities of the para taekwondo players. The secondary objective was to investigate the relationship between some of the proposed factors and the athletes` rankings. METHODS: The data of 556 para taekwondo athletes (119 females and 437 males), who had been classified over the past 5 years, were analyzed. RESULTS: The K44 class was the most popular, and 61% of the classified athletes belonged to this class. Acute injury from trauma was the most frequent cause of impairment, and 62.3% of all impairments/disabilities occurred during 0-5 years of age. Approximately 28% of the athletes had <1 year of training prior to international competitions. One-way analysis of variance performed for the combined length of the upper limbs showed significant differences (F(3,311)=455.78, P<0.001) among the K41-K44 classes. There were weak correlations (p<0.1) between the ranking and the age of the disability/impairment onset, combined length of the upper limbs, and type of disability. CONCLUSIONS: Continued data collection that provides insights into the impairment profiles of para taekwondo athletes is needed to improve the current classification system in order to enhance the safety and fairness.